Positive allosteric modulation of type 1 cannabinoid receptors reduces spike-and-wave discharges in Genetic Absence Epilepsy Rats from Strasbourg. (1st June 2021) - Roebuck, Andrew J.; Greba, Quentin; Smolyakova, Anna-Maria; Alaverdashvili, Mariam; Marks, Wendie N.; Garai, Sumanta; Baglot, Samantha L.; Petrie, Gavin; Cain, Stuart M.; Snutch, Terrance P.; Thakur, Ganesh A.; Hill, Matthew N.; et al.
Abstract: Childhood Absence Epilepsy (CAE) accounts for approximately 10% of all pediatric epilepsies. Current treatments for CAE are ineffective in approximately 1/3 of patients and can be associated with severe side effects such as hepatotoxicity. Certain cannabinoids, such as cannabidiol (CBD), have shown promise in the treatment of pediatric epilepsies. However, CBD remains limited or prohibited in many jurisdictions, and has not been shown to have efficacy in CAE. Modulation of the type 1 cannabinoid receptor (CB1R) may provide more desirable pharmacological treatments. Genetic Absence Epilepsy Rats from Strasbourg (GAERS) model many aspects of CAE, including cortical spike and wave discharges (SWDs). We have recently demonstrated that Δ 9 -tetrahydrocannabinol (THC) increases SWDs in GAERS whereas CBD decreases these events. Here, we characterized aspects of the endocannabinoid system in brain areas relevant to seizures in GAERS and tested whether positive allosteric modulators (PAMs) of CB1R reduced SWDs. Both female and male GAERS had reduced (>50%) expression of CB1R and elevated levels of the endocannabinoid 2-AG in cortex compared to non-epileptic controls (NEC). We then administered the CB1R PAMs GAT211 and GAT229 to GAERS implanted with cortical electrodes. Systemic administration of GAT211 to male GAERS reduced SWDs by 40%. Systemic GAT229 administration reduced SWDs in female and male GAERS. Intracerebral infusion of GAT229 into the cortex of male GAERS reduced SWDs by >60% in a CB1R-dependent manner that was blocked by SR141716A. Together, these experiments identify altered endocannabinoid tone in GAERS and suggest that CB1R PAMs should be explored for treatment of absence seizures. Highlights: GAERS had sex-specific ECS differences compared to non-epileptic controls. Injection of CB1R-PAMs GAT211 or GAT229 reduced spike and wave discharges in GAERS. Cortical infusion of GAT229 reduced spike and wave discharges in GAERS. The CB1R antagonist SR141716A blocked the effects of GAT229. These data suggest CB1R-PAMs may have anticonvulsive properties in GAERS.